Depression and its relation to loneliness and religiosity in Indonesian Muslim adolescents. Issue 3 (15th March 2016) - Purwono, Urip; French, Doran C.
ABSTRACT: This study was initiated to assess the relations between religiosity, depressive symptoms, and loneliness in a sample of 452 Indonesian Muslim 13- and 16-year-old adolescents. Religiosity was operationally defined as participation in required and optional religious activities; Depression was assessed using the Center for Epidemiological Studies Depression Scale; and Loneliness was assessed using the UCLA Loneliness Scale. Religiosity was negatively associated with depression despite controlling for loneliness, gender, and grade. Religiosity was not associated with loneliness, suggesting discriminant validity in the relation between religiously and depression. It is important in future research to examine the mechanisms by which religiosity serves as a protective factor for Indonesian Muslim adolescents.